2021
DOI: 10.3390/nu13124392
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Strain Probiotic Supplementation with a Product Containing Human-Native S. salivarius K12 in Healthy Adults Increases Oral S. salivarius

Abstract: Streptococcus salivarius (S. salivarius) K12 supplementation has been found to reduce the risk of recurrent upper respiratory tract infections. Yet, studies have not reported the effect of supplementation on oral S. salivarius K12 levels or the salivary microbiome. This clinical trial was designed to determine how supplementation with S. salivarius K12 influences the oral microbiome. In a randomized, double-blind, placebo-controlled trial, 13 healthy adults received a probiotic powder (PRO) containing Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Oral–pharyngeal bacteria are swallowed daily and can therefore potentially be detected, albeit at minimal concentrations, also in the faecal microbiota. Indeed, the S. salivarius species is poorly detected in the faecal consortium of subjects affected by COVID-19 [ 19 ]. The authors observed that SIG1 and SIG4, those characterizing the COVID-19 oral microbiota, correlated with the presence of IL-6, a pro-inflammatory cytokine involved in the well-known “cytokine storm” characterizing a severe COVID-19 condition, while SIG2 and SIG3, those characterizing the healthy control oral microbiota, did not [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral–pharyngeal bacteria are swallowed daily and can therefore potentially be detected, albeit at minimal concentrations, also in the faecal microbiota. Indeed, the S. salivarius species is poorly detected in the faecal consortium of subjects affected by COVID-19 [ 19 ]. The authors observed that SIG1 and SIG4, those characterizing the COVID-19 oral microbiota, correlated with the presence of IL-6, a pro-inflammatory cytokine involved in the well-known “cytokine storm” characterizing a severe COVID-19 condition, while SIG2 and SIG3, those characterizing the healthy control oral microbiota, did not [ 17 ].…”
Section: Introductionmentioning
confidence: 99%